Beyond the Mainstream Approaches: Constructivist and Cultural Turns in Indonesian International Relations Scholarship (2015-2025) - Early Nalvi Hoata Sahureka; Ahmad Prasetya Hady (Jurnal Ragam Pengabdian, 2026)
This study examines the extent to which the constructivist turn and the cultural turn are reflected in Indonesian International Relations (IR) journal articles published between 2015 and 2025, and how these turns manifest in scholars’ research topics and analytical approaches. Using a qualitative content analysis of accredited Indonesian IR articles (published in SINTA 1-2 journals), the study finds a post-2015 rise in constructivist-cultural approaches, with the strongest concentration around 2019–2022. The turns manifest across four prominent clusters: (1) cultural diplomacy and soft power; (2) transnational issues and human rights, including advocacy networks and norm diffusion; (3) foreign policy and conflict framed through identity and ideational narratives; and (4) critical security studies, particularly securitization through discourse. While only some articles explicitly label “constructivism”, the majority apply constructivist reasoning implicitly by centering norms, identity, discourse, values, and representation as key explanatory variables. Overall, the findings indicate a substantively plural, contextual, and reflective trajectory in Indonesian IR research between 2015 and 2025.